Contraception for the medically challenging patient - Cwiak, Carrie A.; Allen, Rebecca H. (Springer New York, 2014)
Women with chronic medical problems are at higher risk for complications during pregnancy and, therefore, they are especially in need of appropriate preconception and contraception care. Furthermore, many women with chronic medical problems do not obtain adequate preconception and contraception care. Despite published guidelines by the Centers for Disease Control and Prevention, there is a substantial gap in medical practice regarding the use of contraception in women with co-existing medical problems. Contraception for the Medically Challenging Patient fills the gap that currently exists in the knowledge of correct contraceptive prescribing practice and shows that inappropriate contraindications can easily become a barrier to effective contraception use among women. Chapters highlight obsolete views about appropriate candidates for contraception and address the complex contraceptive needs of today's medically challenging patients with HIV/AIDS, uterine fibroids, or cardiac, neurologic or thyroid disease. The book gives attention to recommendations on the use of contraception in women with medical problems such as diabetes, obesity, epilepsy, and lupus, among others, and provides comprehensive information regarding the effects that certain drugs may have on contraceptive hormone levels. While national guidelines do exist for contraceptive eligibility, this book discusses in more detail the evidence behind the guideline recommendations and the nuances that clinicians confront in daily practice.